Characterization of HIF‐1α/Glycolysis Hyperactive Cell Population via Small‐Molecule‐Based Imaging of Mitochondrial Transporter Activity. Issue 3 (9th January 2018) - Wang, Yang; Liao, Xingyun; Sun, Jianguo; Yi, Bin; Luo, Shenglin; Liu, Tao; Tan, Xu; Liu, Dengqun; Chen, Zelin; Wang, Xin; Shi, Chunmeng
Abstract: The characterization of cancer stem‐like cells (CSCs) has profound implications for elucidating cancer biology and developing treatment strategies. Although surface markers are already used to identify CSCs, the expression of these markers is controversially linked to the phenotypes in different types of tumors and does not represent all functionally relevant of CSCs. Very recently, hyperactive HIF‐1α/glycolysis metabolic pathway is recognized as a master regulator of CSCs. In this study, a near‐infrared fluorescent small‐molecule, IR‐780, is identified for the exclusive characterization of human CSCs through the HIF‐1α/glycolysis dependent mitochondrial transporter ABCB10's activity. The results identified for the first time that ABCB10 is involved in the preferential uptake of IR‐780 in CSCs, which is regulated by HIF‐1α via the direct interaction with the binding site of ABCB10 gene promoter region. In addition, IR‐780 is demonstrated to conjugate with anticancer drug 5‐fluorouracil to act as a potential drug delivery carrier for CSC‐targeted therapy. Thus, the studies provide a new rational approach independent of surface markers to characterize CSCs via small‐molecule‐based imaging of HIF‐1α/glycolysis hyperactive metabolic pathway dependent mitochondrial transporter's activity, which holds promise for the further development of CSCs targeted diagnostic and therapeutic strategies. Abstract : A marker‐independent strategy for the characterization of stem‐like cells (CSCs) is developed by targeting hyperactive HIF‐1α/glycolysis metabolic pathway via molecular imaging of mitochondrial transporter ABCB10's activity by near‐infrared fluorescent small‐molecule IR‐780. This represents a potential drug delivery strategy for the future development of CSC‐targeting diagnostic and therapeutic modalities.